2021
DOI: 10.1111/jth.15497
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic form of Factor VIII to prevent inhibitor development in the treatment of Hemophilia A

Abstract: Background:The development of antidrug antibodies, also termed inhibitors, against administered factor VIII (FVIII) is one of the major complications in the clinical management of hemophilia A. Once formed, these inhibitory antibodies abrogate the activity of FVIII, resulting in loss of hemostatic efficacy and patients are subjected to increased risk of bleeding tendencies. Current treatment options after inhibitor development are expensive and ineffective in some cases. Therefore, treatment strategies that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In murine HA models, researchers found that phosphatidylserine (PS) induced immune tolerance and reduced the production of inhibitors by affecting the maturation of DCs, inducing the generation of Tregs, and inhibiting the generation of memory B cells ( 68 70 ). More recently, studies have demonstrated that the binding of FVIII to lysophosphatidylserine (Lyso-PS) to form the Lyso-PS-rFVIII Fc complex significantly reduced inhibitor development in HA mice after either intravenous or oral administration of Lyso-PS ( 71 , 72 ). In addition, researchers found that site N2118, containing high-mannose glycans, have a significant impact on FVIII immunogenicity in the murine HA model ( 73 ).…”
Section: Pathophysiology Of Fviii Inhibitor Developmentmentioning
confidence: 99%
“…In murine HA models, researchers found that phosphatidylserine (PS) induced immune tolerance and reduced the production of inhibitors by affecting the maturation of DCs, inducing the generation of Tregs, and inhibiting the generation of memory B cells ( 68 70 ). More recently, studies have demonstrated that the binding of FVIII to lysophosphatidylserine (Lyso-PS) to form the Lyso-PS-rFVIII Fc complex significantly reduced inhibitor development in HA mice after either intravenous or oral administration of Lyso-PS ( 71 , 72 ). In addition, researchers found that site N2118, containing high-mannose glycans, have a significant impact on FVIII immunogenicity in the murine HA model ( 73 ).…”
Section: Pathophysiology Of Fviii Inhibitor Developmentmentioning
confidence: 99%
“…2 Furthermore, healthy individuals with no genetic disruption to FVIII may also spontaneously develop FVIII inhibitory antibodies resulting in acquired hemophilia. 3 Guided by structural studies of FVIII, recent bioengineering efforts have inspired the development of new molecules to bypass or replace extant FVIII therapeutic products, including bispecific antibodies that form active tenase complexes, 4,5 FVIII molecules that are either deimmunized or do not cross-react with anti-human FVIII antibodies, [6][7][8][9] and FVIII preparations with extended plasma half-lives. [10][11][12]…”
mentioning
confidence: 99%